2005
DOI: 10.1038/nmeth749
|View full text |Cite
|
Sign up to set email alerts
|

In vivo protein labeling with trimethoprim conjugates: a flexible chemical tag

Abstract: The introduction of green fluorescent protein and its variants (GFPs) has allowed protein analysis at the level of the cell. Now, chemical methods are needed to label proteins in vivo with a wider variety of functionalities so that mechanistic questions about protein function in the complex cellular environment can be addressed. Here we demonstrate that trimethoprim derivatives can be used to selectively tag Escherichia coli dihydrofolate reductase (eDHFR) fusion proteins in wild-type mammalian cells with mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
238
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(239 citation statements)
references
References 17 publications
0
238
1
Order By: Relevance
“…Heterodimeric conjugates of the common antibiotic trimethoprim (TMP) covalently linked to various terbium chelates were developed that bind noncovalently to eDHFR. TMP and eDHFR interact exclusively with one another in mammalian systems, and this interaction has been previously exploited to develop TMP-fluorophore conjugates that specifically label eDHFR fusion proteins in a variety of wild-type mammalian cell lines (LigandLink™ Universal Labeling Technology, Active Motif, Inc.) (33)(34)(35). In our previous study, we found that one particular conjugate, TMP-Lumi4 ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Heterodimeric conjugates of the common antibiotic trimethoprim (TMP) covalently linked to various terbium chelates were developed that bind noncovalently to eDHFR. TMP and eDHFR interact exclusively with one another in mammalian systems, and this interaction has been previously exploited to develop TMP-fluorophore conjugates that specifically label eDHFR fusion proteins in a variety of wild-type mammalian cell lines (LigandLink™ Universal Labeling Technology, Active Motif, Inc.) (33)(34)(35). In our previous study, we found that one particular conjugate, TMP-Lumi4 ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…To overcome this limitation for further applications, methotrexate was substituted with the antibiotic trimethoprim (TMP). TMP binds to eDHFR with high affinity (1 nM K D ) but exhibits minimal binding to mammalian DHFR (K D > 1 mM) [17]. It has been demonstrated that trimethoprim conjugates can be used to selectively label eDHFR in wild type mammalian cells.…”
Section: Noncovalent Protein Tagsmentioning
confidence: 99%
“…The 18 kDa monomeric eDHFR behaves well when expressed in mammalian cells, and TMP-fluorophore conjugates with standard linker and protection group chemistry show good cell permeability. Labeling of nuclear proteins, plasma membrane proteins, and cytoplasmic proteins have been demonstrated in various cell types, showing that the eDHFR-TMP receptor-ligand pair can be used as a robust noncovalent protein labeling system in living cells [17][18]. The TMP-tag is marketed as LigandLink by Active Motif (Carlsbad, CA).…”
Section: Noncovalent Protein Tagsmentioning
confidence: 99%
“…Two types of technology stand out for their high performance. The first is a series of 'protein-directed' labeling techniques including DHFR [28], SNAP-tag [29], CLIP-tag [29], and Halo-tag [30]-based conjugations. The conjugations between these proteins and their substrates exhibit high selectivity and high affinity, even within cells and cell extracts [24].…”
Section: Box 1 Labeling Proteins With Organic Fluorophores Within Celmentioning
confidence: 99%